Study of Multi-Cracked Cantilever Composite Beams Subjected to External Moving Load - Husseina, Nazhad Ahmad; Ahmadb, Sara Mohamad; Mohammed, Dilshad A. (Anbar Journal of Engineering Sciences, 2019)
The behaviour of multiple cracked cantilever composite beams is studied when subjected to moving periodic force. In this investigation a new model of multiple cracked composite beams under periodic moving load is solved. Three cracks are considered at different position of the beam for numerical solution. The results from experimental work compared to numerical solution. The multiple cracks are identified easily from the deflection graphs at different force speed. Influences of crack depth at different load speed are investigated